In Vitro Dissolution and In Vivo Bioequivalence Evaluation of Two Metformin Extended‐Release Tablets. Issue 4 (24th July 2020) - Zhou, Ziye; Wang, Chenxiang; Li, Min; Lan, Qin; Yu, Chao; Yu, Guoxin; Xia, Yan; Chen, Huafang; Zhang, Xiuhua
Abstract: The objective of the present study was to evaluate the bioequivalence between generic and branded metformin extended‐release (ER) tablets in Chinese subjects. We tested bioequivalence in vitro and in vivo using a comparative dissolution study and a comparative pharmacokinetic trial. Safety assessments were conducted throughout the entire trial period. The dissolution profiles of the generic formulation expressed obvious extended‐release properties, similar to those of the branded formulation ( f 2 > 60.0%). Consistent with the result of the in vitro study, no remarkable differences were found in terms of pharmacokinetic profiles between generic and branded formulations. The 90% confidence intervals of Ln AUC0‐36 h, Ln AUC0‐∞, and Ln Cmax from generic formulation versus branded formulation were 91.4% to 105.0%, 91.3% to 104.7%, and 101.2% to 119.4%, respectively. During the entire trial period, 4 subjects experienced 11 adverse events. All these were mild and spontaneously resolved. The results obtained from the present study suggest that the generic and branded metformin ER tablets were bioequivalent in Chinese subjects.